2011
DOI: 10.1002/sd.519
|View full text |Cite
|
Sign up to set email alerts
|

How Children Come to Understand Sustainable Development: A Contribution to Educational Agenda

Abstract: This study provides an interdisciplinary account determining how children and adolescents understand urban and architectural aspects of sustainable development. The concept of sustainability implies complex relations between ethical, economical, social, technical and other qualities of our environment. The concept is difficult to understand for children who lack the abilities of abstract reasoning and multi-dimensional thinking. A new measure of sustainability understanding was formed based on pictorial rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Regarding females, theoretical justification comes from the argument that women, based on sex role differences and social development, deliberate on their impact on others and the environment to a higher extent than men (Eagly, 1987, as cited by Straughan and Roberts, 1999). Recently, it was also found that girls had higher levels of appreciation for sustainability issues than boys (Svetina et al, 2013). In this regard it can be argued that the morality of care that Gilligan (1982) put forth extends from caring for other humans to the environment and thus climate change as well.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…Regarding females, theoretical justification comes from the argument that women, based on sex role differences and social development, deliberate on their impact on others and the environment to a higher extent than men (Eagly, 1987, as cited by Straughan and Roberts, 1999). Recently, it was also found that girls had higher levels of appreciation for sustainability issues than boys (Svetina et al, 2013). In this regard it can be argued that the morality of care that Gilligan (1982) put forth extends from caring for other humans to the environment and thus climate change as well.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…Then, based on the fact that abstract based concepts of sustainability are quite complex to be understood by children, trainers have to look for ways to make it easier and more tangible [17]. Consequently, this work proposed to teach the circular economy challenges with the analysis of a well-known material that children can identify with easily, aluminium.…”
Section: Introductionmentioning
confidence: 99%
“…These programmes are excellent examples of directions in which education for sustainable development could and should go, in particular for the post‐communistic countries, where awareness of the value of rivers is being slowly awakened (see, e.g., Crotty and Hall, ). It is also important that such programmes help to build the identity of young generations, shared responsibility for the rivers and understanding of the concept of sustainable development (see, e.g., Pulinowa, ; Angiel, , , ; Svetina et al ., ). The Vistula is commonly described as the last big wild river in this part of Europe. Therefore, the authors are careful in comparing this river and findings of this study to other rivers.…”
Section: Discussionmentioning
confidence: 97%